Disclosure of COSO Framework, Firm Size, Institutional Ownership, Profitability, and Leverage in Property Companies on JII70 - Zuraidah, Zuraidah; Puwandani, Eranikan Rahma; Ramadhany, Nerisha Putri; Nawirah, Nawirah (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This research aims to examine the disclosure of the COSO ERM-Framework in Property Sector Companies listed on the Jakarta Islamic Index 70 (JII70) and empirically demonstrate the influence of firm size, institutional ownership, profitability, and leverage on ERM data of Property Sector Companies listed on the Jakarta Islamic Index 70. The study adopts a quantitative method, utilizing secondary data obtained from the Jakarta Islamic Index 70 website. The sample consists of 9 property sector companies. Data collection is conducted through time series data from 2018 to 2022, while data analysis employs linear regression. This research can serve as a reference for each company to be more cautious in implementing policies, and it is expected that management will intensify and implement ERM in their respective businesses to facilitate better risk management for property sector companies in JII70. The difference between this research and previous studies lies in the variables and companies under examination. Previous research tends to focus on manufacturing or non-financial companies as subjects, whereas this study selects Property Sector Companies listed on JII70 as its subject. Because the property sector company is a business sector that dominates the sub-sectors in JII70. The findings of this research indicate that, partially, firm size, institutional ownership, profitability, and leverage do not have a significant effect on the COSO ERM-Framework. However, based on the research results, it is evident that firm size, institutional ownership, profitability, and leverage collectively have an impact on the COSO ERM-Framework.